A biochemical definition of cure after brachytherapy for prostate cancer. (August 2020) - Crook, Juanita M.; Tang, Chad; Thames, Howard; Blanchard, Pierre; Sanders, Jeremiah; Ciezki, Jay; Keyes, Mira; Morris, W. James; Merrick, Gregory; Catton, Charles; Raziee, Hamid; Stock, Richard; et al.
Highlights: Close to 80% of men 4–5 years after LDR prostate brachytherapy will achieve a PSA of 0.2 ng/ml or less. PSA ≤ 0.2 ng/ml is associated with 97–99% freedom from prostate cancer recurrence at 10–15 years. This applies across all risk groups and to LDR brachytherapy alone or combined with ADT and/or EBRT. Abstract: Background and purpose: To identify a PSA threshold value at an intermediate follow-up time after low dose rate (LDR) prostate brachytherapy associated with cure, defined as long-term (10–15 year) freedom from prostate cancer. Materials and methods: Data from 7 institutions for 14, 220 patients with localized prostate cancer treated with LDR brachytherapy, either alone (8552) or with external beam radiotherapy ( n  = 1175), androgen deprivation ( n  = 3165), or both ( n  = 1328), were analyzed. Risk distribution was 42.4% favorable, 49.2% intermediate, and 8.4% high-risk. Patients with clinical failure before 3.5 years were excluded. Kaplan-Meier analysis was used with clinical failure (local, distant, regional or biochemical triggering salvage) as an endpoint for each of four PSA categories: PSA ≤ 0.2, >0.2 to ≤0.5, >0.5 to ≤1.0, and >1.0 ng/mL. PSA levels at 4 years (±6 months) in 8746 patients without clinical failure were correlated with disease status at 10–15 years. Results: For the 77.1% of patients with 4-year PSA ≤ 0.2, the freedom-from-recurrence (FFR) rates were 98.7% (95% CI 98.3–99.0) at 10 years and 96.1% (95% CI 94.8–97.2) at 15 years. Three independent validation cohorts confirmed 97–99% 10-year FFR rates with 4-year PSA ≤ 0.2. Successive PSA categories were associated with diminished disease-free rates at 10 and 15 years. PSA category was strongly associated with treatment success ( p  < 0.0005). Conclusions: Since 98.7% of patients with PSA ≤ 0.2 ng/mL at 4 years after LDR prostate brachytherapy were disease-free beyond 10 years, we suggest adopting this biochemical definition of cure for patients with ≥4 years' follow-up after LDR brachytherapy.